Teaching vocabulary to young learners through developing language skills - Turayeva Umida (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2024)
The essential part of the article is based on the material of theory and practice of teaching foreign languages. Thus, the main aim of the article is to present new methods of teaching such language aspects as vocabulary. Moreover, such essential points of teaching process as lesson plan, evaluation, motivation and testing are deeply demonstrated in the article. The article reveals actual points of teaching foreign languages, which make the teaching process easy, motivated, interesting and effective. The following article can be used at the lessons of integrated study skills, and in the further professional activity of Master students. The basic part of the work is the presentation of modern and effective ways and methods of teaching foreign languages, educational and pedagogical technologies. The article will help to create competent, effective and qualified teachers of foreign languages.